Providing practical support for people with autism spectrum disorder : supported living in the community - Edwards, Denise (Jessica Kingsley Publishers, 2008)
One element at the heart of effective service provision is an understanding of the service user's needs. This book unravels some of the common misunderstandings between people with autism spectrum disorders (ASD) and providers of support services, and offers practical advice on how to ensure that the needs of people with ASD are catered for effectively. Denise Edwards writes directly from her own experiences of finding appropriate support for her adopted son, John Paul, who has Asperger's syndrome, but also draws on the experiences of a broad range of service users. She emphasises the importan.